Incidence of palmaris longus agenesis in second year medical students of IIUM, 2011/2012 - Tun, Ye; Myint, Yi Yi (2012)
The palmaris longus (PL) is one of the most variable muscles of the human body. The individuals may have unilateral or bilateral absence of PL, varies with ethnicity, gender and side of the body. An understanding of its variations is useful as it is often used as tendon graft for reconstructive surgery because of its little functional use and short belly and long, cord-like tendon. The aims of this study are to: 1. determine the incidence of unilateral and bilateral absence of palmaris longus in second year medical students of IIUM and to correlate it with gender, dominant hand and body side. 2. compare the results of five clinical techniques to detect the palmaris longus by using the Likert scale. The presence of the PL tendon was clinically determined in 128 second year medical students, IIUM, 2011/2012 using the standard (Schaeffer’s), Mishra II, Gangata, Pushpakumar and lotus techniques. The Likert scale was used to compare the results of the five clinical techniques. If all of the above techniques failed to demonstrate a palmaris longus tendon, it was considered absent. The presence or absence of the palmaris longus tendon was recorded for both sides. Relationships between tendon absence, body side, hand dominance and gender were recorded. The overall prevalence of absence of the PL was 8(6.25%). Unilateral absence of the PL was recorded in 5 (3.91%) and bilateral in 3 (2.34%) study subjects. According to body side, the unilateral absence was found only on the right side and also on right handed person. It was all female subjects. The standard (Schaeffer’s) method in male subjects and Gangata method in female subjects are most obviously seen the palmaris longus. This useful palmaris longus as a donor tendon is present in the vast majority of second year medical students of IIUM 2011/2012(93.75%).